Tuning the Reactivity of Functionalized Diallylic Alcohols: Brønsted versus Lewis Acid Catalysis. Issue 43 (19th July 2017) - Lempenauer, Luisa; Duñach, Elisabet; Lemière, Gilles
Abstract: The chemodivergent reactivity of bifunctional, enol thioether‐containing diallylic alcohols in acidic medium is disclosed, highlighting the difference between strong Lewis acid and mild Brønsted acid catalysis. In the presence of bismuth(III) triflate, allylic alcohol activation affords diversely substituted cyclopentenones in a Nazarov‐type electrocyclization, whereas activation of the thioenol ether by p ‐toluenesulfonic acid provides an entry to α‐sulfenylated β, γ‐unsaturated ketones. Both methods represent a facile access to the corresponding products under mild conditions, using inexpensive and non‐toxic catalytic systems. Abstract : Let the acid decide : The chemodivergent reactivity of bifunctional enol thioether‐containing diallylic alcohols is described, hereby highlighting the difference between mild Brønsted acid and strong Lewis acid catalysis.